2019
DOI: 10.1177/0146167219867965
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Face and Voice Cues in Predicting the Outcome of Student Representative Elections

Abstract: First impressions formed after seeing someone’s face or hearing their voice can affect many social decisions, including voting in political elections. Despite the many studies investigating the independent contribution of face and voice cues to electoral success, their integration is still not well understood. Here, we examine a novel electoral context, student representative ballots, allowing us to test the generalizability of previous studies. We also examine the independent contributions of visual, auditory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 51 publications
1
31
1
1
Order By: Relevance
“…Such snap judgements can often be made within milliseconds, but are nonetheless known to affect our behaviours, attitudes and decisions (Bar, Neta, & Linz, 2006;McAleer et al, 2014;Willis & Todorov, 2006). Most importantly, this is true in a range of situations, even when we have access to additional and more relevant information -from choosing who to vote for in the upcoming elections, to deciding the length and severity of court sentences, or the Airbnb host we decide to stay with (Chen, Halberstam, & Yu, 2016;Ert, Fleischer, & Magen, 2016;Klofstad, 2016;Mileva et al, 2020;Sussman, Petkova, & Todorov, 2013;Tigue, Borka, O'Connor, Schandl & Feinberg, 2012;Wilson & Rule, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Such snap judgements can often be made within milliseconds, but are nonetheless known to affect our behaviours, attitudes and decisions (Bar, Neta, & Linz, 2006;McAleer et al, 2014;Willis & Todorov, 2006). Most importantly, this is true in a range of situations, even when we have access to additional and more relevant information -from choosing who to vote for in the upcoming elections, to deciding the length and severity of court sentences, or the Airbnb host we decide to stay with (Chen, Halberstam, & Yu, 2016;Ert, Fleischer, & Magen, 2016;Klofstad, 2016;Mileva et al, 2020;Sussman, Petkova, & Todorov, 2013;Tigue, Borka, O'Connor, Schandl & Feinberg, 2012;Wilson & Rule, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that they reflect general, stereotyped aspects of person perception (McAleer, et al ., 2014; Todorov, Said, Engell, Oosterhof, 2008). Even though first impressions tend to not be accurate, they are important because they have been shown to predict behaviour and influence decision‐making (see Olivola, Funk, & Todorov, 2014, for a review) in a number of different contexts, such as election outcomes (Ballew & Todorov, 2007; Klofstad, 2016; Klofstad, Anderson, & Peters, 2012; Mileva, Tompkinson, Watt, & Burton, 2020; Sussman, Petkova, & Todorov, 2013; Todorov, Mandisodza, Goren, & Hall, 2005), applicant success at job interviews (see Harris & Garris, 2008, for a review), and court sentencing (Wilson & Rule, 2015; Zebrowitz & McDonald, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In sum, our series of experiments further highlight the importance of within-person variability for understanding both face and voice perception. Although humans appear to treat impressions of the social traits of others as proxies for evaluations of stable personality characteristics (Chen et al 2016;Ert et al, 2016;Klofstad, 2016;Mileva et al, 2020;Sussman et al, 2013;Wilson & Rule, 2015), we show that transient changes in the physical properties of faces and voices lead to concomitant changes in social trait evaluations. Thus, we consistently observed that within-person variability in trait evaluations is at least on par with the between-person variability.…”
Section: Discussionmentioning
confidence: 72%
“…Such snap judgements can often be made within milliseconds, but are nonetheless known to affect our behaviours, attitudes and decisions (Bar, Neta, & Linz, 2006;McAleer et al, 2014;Willis & Todorov, 2006). Most importantly, this is true in a range of situations, even when we have access to additional and more relevant information -from choosing who to vote for in the upcoming elections, to deciding the length and severity of court sentences or the Airbnb host we decide to stay with (Chen, Halberstam, & Yu, 2016;Ert, Fleischer, & Magen, 2016;Klofstad, 2016;Mileva et al, 2020;Sussman, Petkova, & Todorov, 2013;Tigue, Borka, O'Connor, Schandl & Feinberg, 2012;Wilson & Rule, 2015). Despite their impact on many aspects of our lives, such social trait evaluations are unlikely to be firmly grounded in truth, and the evidence for their accuracy is limited (Klofstad & Anderson, 2018;Todorov, 2017).…”
Section: Introductionmentioning
confidence: 99%